Hierarchical microstructure and strengthening mechanisms of a CoCrFeNiMn high entropy alloy additively manufactured by selective laser melting. (September 2018) - Zhu, Z.G.; Nguyen, Q.B.; Ng, F.L.; An, X.H.; Liao, X.Z.; Liaw, P.K.; Nai, S.M.L.; Wei, J.
Abstract: A near-fully dense CoCrFeNiMn high entropy alloy was additively manufactured by selective laser melting successfully. The as-built samples exhibit a hierarchical structure, including melt pools, columnar grains, sub-micron cellular structures, and dislocations. An outstanding combination of high strength and excellent ductility compared to those fabricated by conventional methods was achieved in the as-built samples. Quantitative analysis revealed that the cellular structures contribute significantly to the enhanced strength through dislocation hardening rather than cellular boundary strengthening. The excellent ductility is correlated with the steady strain hardening controlled by the sophisticated dislocation activities. Graphical abstract: Unlabelled Image